Church of St. John in Stivanje polje on Dugi otok (In situ, 2025)
The paper describes the results of the seventh campaign of archaeological research around the church of St. John in Stivanje polje within the Telašćica Nature Park. In addition to several medieval graves, an older, previously unrecorded, burial horizon was also recognized, dated to the 4th and 5th centuries.
Keywords: Sv. Ivan; Stivanje polje; Telašćica; Dugi otok; church; medieval graveyard; Roman farming complex